Survival of rapidly fluctuating natural low winter temperatures by High Arctic soil invertebrates. (December 2015) - Convey, Peter; Abbandonato, Holly; Bergan, Frode; Beumer, Larissa Teresa; Biersma, Elisabeth Machteld; Bråthen, Vegard Sandøy; D'Imperio, Ludovica; Jensen, Christina Kjellerup; Nilsen, Solveig; Paquin, Karolina; Stenkewitz, Ute; Svoen, Mildrid Elvik; et al.
Abstract: The extreme polar environment creates challenges for its resident invertebrate communities and the stress tolerance of some of these animals has been examined over many years. However, although it is well appreciated that standard air temperature records often fail to describe accurately conditions experienced at microhabitat level, few studies have explicitly set out to link field conditions experienced by natural multispecies communities with the more detailed laboratory ecophysiological studies of a small number of 'representative' species. This is particularly the case during winter, when snow cover may insulate terrestrial habitats from extreme air temperature fluctuations. Further, climate projections suggest large changes in precipitation will occur in the polar regions, with the greatest changes expected during the winter period and, hence, implications for the insulation of overwintering microhabitats. To assess survival of natural High Arctic soil invertebrate communities contained in soil and vegetation cores to natural winter temperature variations, the overwintering temperatures they experienced were manipulated by deploying cores in locations with varying snow accumulation: No Snow, Shallow Snow (30 cm) and Deep Snow (120 cm). Air temperatures during the winter period fluctuated frequently between +3 and −24 °C, and the No Snow soil temperatures reflected this variation closely, with the extreme minimum being slightly lower. Under 30 cm of snow, soil temperatures varied less and did not decrease below −12 °C. Those under deep snow were even more stable and did not decline below −2 °C. Despite these striking differences in winter thermal regimes, there were no clear differences in survival of the invertebrate fauna between treatments, including oribatid, prostigmatid and mesostigmatid mites, Araneae, Collembola, Nematocera larvae or Coleoptera. This indicates widespread tolerance, previously undocumented for the Araneae, Nematocera or Coleoptera, of both direct exposure to at least −24 °C and the rapid and large temperature fluctuations. These results suggest that the studied polar soil invertebrate community may be robust to at least one important predicted consequence of projected climate change. Highlights: Overwintering survival of Arctic soil invertebrates in the natural environment. With no snow cover soil temperatures dipped to below −26 °C and fluctuated between 0 and −24 °C. Temperatures under deep snow were stable and close to 0 °C. No differences in invertebrate survival observed between snow depth manipulations. Implications for interpretation of laboratory experiments and climate change responses.